2020
DOI: 10.2196/20185
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Behavior of College Students During the Early Phases of the COVID-19 Pandemic: Longitudinal Smartphone and Ecological Momentary Assessment Study

Abstract: Background The vast majority of people worldwide have been impacted by coronavirus disease (COVID-19). In addition to the millions of individuals who have been infected with the disease, billions of individuals have been asked or required by local and national governments to change their behavioral patterns. Previous research on epidemics or traumatic events suggests that this can lead to profound behavioral and mental health changes; however, researchers are rarely able to track these changes wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
508
12
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(575 citation statements)
references
References 28 publications
39
508
12
16
Order By: Relevance
“…While it is possible that the types of physical activities that students were participating in changed, for example, the shut-down of activity centers such as indoor gyms may have resulted in increases in outdoor physical activities or in-home exercise, this does not seem to have led to more overall minutes of physical activity. This is consistent with Huckins and colleagues who used motion sensors in smart phones to track college student's pre-and post-COVID-19 changes and found students to be more sedentary [14], and with Tison and colleagues who used daily step counts from smart phone accelerometers and found that steps decreased worldwide after the declaration of the global pandemic [63]. This particular nding is concerning, as physical activity has consistently been found to prevent depression [43] and reduce depression symptoms in those with mental illness [44].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While it is possible that the types of physical activities that students were participating in changed, for example, the shut-down of activity centers such as indoor gyms may have resulted in increases in outdoor physical activities or in-home exercise, this does not seem to have led to more overall minutes of physical activity. This is consistent with Huckins and colleagues who used motion sensors in smart phones to track college student's pre-and post-COVID-19 changes and found students to be more sedentary [14], and with Tison and colleagues who used daily step counts from smart phone accelerometers and found that steps decreased worldwide after the declaration of the global pandemic [63]. This particular nding is concerning, as physical activity has consistently been found to prevent depression [43] and reduce depression symptoms in those with mental illness [44].…”
Section: Discussionsupporting
confidence: 88%
“…They also reported increases in anxiety and depression, and academic performance suffering due to mental health concerns [12]. These results are consistent with ndings by Huckins and colleagues, who found that U.S. college students exhibited greater anxiety and depression and increased sedentary behavior in the rst few months of the COVID-19 pandemic [14]. Because of the major stressors associated with COVID-19, such as the imposition of unfamiliar public health measures, potential nancial losses, and the reality of life in a pandemic, there will likely be an uptick in psychiatric illness in the general population [15].…”
Section: Introductionsupporting
confidence: 87%
“…In the face of global concern about the mental health effects of COVID-19, specifically in adolescents and young adults (Fegert et al 2020), few studies have sought to document and characterize loneliness and mental health wellbeing and problems in the young adult population. To date, only anxiety, post-traumatic stress disorder, and depression have been documented among college students in China and the US (Cao et al 2020;Chang, Yuan, and Wang 2020;Huckins et al 2020). Recent reports on loneliness during COVID-19 have yielded controversial results, and differences between subpopulations evaluated (Killgore et al 2020;Luchetti et al 2020;Sutin, Luchetti, and Terracciano 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies included in the review were cross-sectional and it is therefore challenging to determine how mental health status evolved in the early months of the pandemic. For university students speci cally, there are some studies indicating short-term increases in depression and anxiety during COVID-19 [5,6], while others have found no changes [7]. Moreover, it is plausible that the mental health impact of the pandemic differs between regions and countries, as well as between sub-groups within populations.…”
Section: Introductionmentioning
confidence: 99%